Interpersonal psychological well-being among coach-athlete-sport psychology practitioner triads - Simpson, R. A. C.; Didymus, F. F.; Williams, T. L. (Psychology of Sport and Exercise, 2023)
The importance of psychological well-being (PWB) is widely acknowledged in global policy and has important ramifications for health, performance, and engagement among sport performers. Despite this compelling knowledge, little is known about PWB in close sport relationships. We aimed to explore the interpersonal antecedents, transfer mechanisms, and outcomes of PWB within and among athletes, coaches, and sport psychology practitioners (SPPs). Underpinned by an interpretative paradigm, we conducted individual and triadic interviews with three coach-athlete-SPP triads from individual sports and analyzed data using abductive reasoning applied to reflexive thematic analysis. The themes we constructed relating to antecedents of PWB were situational properties of stressors, factors relating to the organization, shared values and characteristics, and interpersonal resilience. PWB was transferred among the triad via interpersonal coping, emotional contagion, and social appraising. PWB was cyclic in nature and, thus, we constructed themes (i.e., psychological safety, meaningful experiences of growth and development, and relational dynamics), which represented those factors that acted as both antecedents and outcomes. Our findings transcend individual understandings of PWB in sport by representing the first interpersonal examination of PWB among coach-athlete-SPP triads. This shift is crucial for informing how performers can collectively evaluate and manage PWB in the context of their close sport relationships. These findings implicate two primary recommendations: first, we recommend that researchers extend conceptual understanding of PWB among those in close sport relationships. Second, organizations and practitioners are encouraged to consider how mentoring and relationship-building schemes can be tailored within wider education and support programs to bolster PWB among athletes, coaches, and practitioners.